Aerodynamic body position of the brakeman of a 2-man bobsleigh - Chowdhury, H.; Loganathan, B.; Alam, F. (Procedia Engineering, 2015)
This paper examines the aerodynamic behaviour of a standard 2-man bobsleigh including the crews. The body position of the brakeman was studied over a range of angles from 25 to 90 degrees relative to the wind direction. Wind tunnel experiments were undertaken on a 50% scale model of 2-man bobsleigh and the crews. Aerodynamic drag forces were measured over a range of wind speeds (40 to 120 km/h) in the wind tunnel environment. Additionally, wool tufts and smoke were used to visualise the airflow characteristics around the bobsleigh and crews. The results show that the body inclination angle of the brakeman has significant effect on the overall aerodynamics of bobsleighing and the most aerodynamic body position of the brakeman was found at 55 degree with the minimal drag. The results also indicate that this particular body position of the brakeman can reduce the drag over 10% compared to his body position at 90 degree. However, the brakeman's body position over 35 degree indicates an increase of drag.